Refractive index biosensor based on offset technique of coreless fiber - Aldulimi, Saraa J.; Taher , Hanan J. (Iraqi Journal of Laser, 2024)
This paper suggested a biosensor structure using an offset technique between two similar coreless fiber (CF) segments spliced between two single-mode fibers (SMF) for refractive index (RI) measurement of the liquid pharmaceutical, where experimented with different lengths of CF sections for 10 mm, 15mm, 20 mm, and 25 mm with different offsets for  2.6 μm, 6.4 μm, and 18.3 μm of symmetric CF sections. This sensor tests different refractive indices (1, 1.333, 1.337, 1.369, 1.393) of liquid pharmaceuticals The wavelength shifting increases with decreasing length or displacement of offset. The highest sensitivity was achieved, 255.5 nm/RIU, with the smallest sensor size, corresponding to the highest refractive index of 1.393 for the Histadin syrup drug, obtained using the optimal length and offset. This sensor has the capability to detect various refractive indices of chemicals and biochemical liquids. Advantages of the proposed sensor include high sensitivity, adaptability, enabling faster real-time measurements, ease of manufacturing and operation, compact size, lightweight design, and low cost.